Relationship between the Mediterranean diet and risk of hepatic fibrosis in patients with non-alcoholic fatty liver disease: A cross-sectional analysis of the RaNCD cohort - Miryan, Mahsa; Darbandi, Mitra; Moradi, Mozhgan; Najafi, Farid; Soleimani, Davood; Pasdar, Yahya (Frontiers in Nutrition, 2023)
Background: Despite evidence supporting the beneficial effects of the Mediterranean diet (MedDiet) on hepatic steatosis in subjects with non-alcoholic fatty liver disease (NAFLD), the relationship of the MedDiet with hepatic fibrosis is as yet unclear. The aim of the present study was to explore this association in Iranian adults with NAFLD. Methods: This cross-sectional study included 3325 subjects with NAFLD from the Ravansar Noncommunicable Disease (RaNCD) cohort. Dietary intake data were collected by a validated food frequency questionnaire (FFQ). The MedDiet score was computed based on a nine-point scale constructed by Trichopoulou et al. Fatty liver index (FLI) and fibrosis-4 (FIB-4) index were used to predict hepatic steatosis and fibrosis in the population. Multivariate regression models were applied to determine associations. Results: Subjects in the highest tertile of MedDiet score had a higher platelet and a lower weight, total cholesterol (TC), LDL-c, and FLI than those in the lowest tertile (P-value <0.05). Adherence to the MedDiet was associated with a 7.48 (95%CI: 5.376 to 9.603) ×103/µL; -0.417 (-0.819 to -0.014) kg, -2.505 (-3.835 to -1.175) mg/dL; and -1.93 (-2.803 to -1.061) mg/dL change in platelet, weight, TC, and LDL-c for each SD increase in the score, respectively. A significant linear trend was observed in odds of hepatic fibrosis across the tertiles of the MedDiet score (P-trend:0.008). This linear trend was attenuated but remained significant after the adjustment of the relevant confounders (P-trend:0.032). Adherence to the MedDiet was independently associated with about 16% lower odds of having hepatic fibrosis in patients with NAFLD for each SD increase in the score. Conclusion: Adherence to the MedDiet characterized by a high intake of whole grains, fruits, vegetables, legumes, nuts, and fish was associated with a lower risk of having hepatic fibrosis in patients with NAFLD. Further studies are required to elucidate the causal relationship of observed association in individuals of all ages, ethnicities, and etiologies of hepatic steatosis.